Mechanism Underlying Levofloxacin Uptake by Human Polymorphonuclear Neutrophils - Vazifeh, Doina (American Society for Microbiology, 1999)
The mechanism of radiolabeled levofloxacin ([(3)H]levofloxacin) uptake by human polymorphonuclear neutrophils (PMNs) was investigated by a classical velocity centrifugation technique. PMNs were incubated with levofloxacin for 5 to 180 min under various conditions before centrifugation through an oil cushion. Radioactivity was measured in the cell pellet to determine the amount of cell-associated drug. The uptake of levofloxacin was moderate with a cellular concentration/extracellular concentration ratio of about 4 to 6. Levofloxacin accumulated in PMNs parallel to the extracellular concentration, without saturation, over the range of 2.5 to 200 mg/liter (linear regression analysis: r = 0.92; P < 0.001). The activation energy was low (36 ± 7.2 kJ/mol). Levofloxacin uptake was increased in Ca(2+)-depleted, EGTA-containing medium by approximately 33% (P = 0.022), while Ni(2+), a Ca(2+) channel inhibitor, inhibited it in a concentration-dependent manner, with the concentration that inhibited 50% of control uptake being approximately 2.65 mM. Verapamil (an l-type Ca(2+) channel inhibitor) and other pharmacologic agents which modify Ca(2+) homeostasis did not modify levofloxacin uptake. Interestingly, Ca(2+) and Mg(2+) inhibited levofloxacin uptake in a concentration-dependent manner. EGTA, Ni(2+), and verapamil did not modify levofloxacin efflux; thapsigargin, a Ca(2+) pool-releasing agent, modestly increased the intracellular retention of levofloxacin. In addition, contrary to other fluoroquinolones, probenecid at 1 to 10 mM did not modify either levofloxacin uptake or efflux. These data are consistent with a mechanism of passive accumulation of levofloxacin in PMNs. Extracellular Ca(2+) and Mg(2+) may influence the structural conformation of levofloxacin or the lipophilicity of PMN membranes, thus explaining their effect on levofloxacin uptake.